1979
DOI: 10.1007/bf03006163
|View full text |Cite
|
Sign up to set email alerts
|

Pancuronium for rapid induction technique for tracheal intubation

Abstract: A PATIEN'F with a full stomach who requires anaesthesia for an emergency operation or an obstetrical procedure is frequently managed by a rapid induction (crash) technique. This technique ordinarily includes the use of suxamethonium to provide relaxation of the jaw so that tracheal intubation can be accomplished quickly. There are a number of conditions, however, that contraindicate the use of suxamethonium. These conditions include genetic abnormalities, central nervous system lesions that result in muscle at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Higher than normal doses of antagonists or nondepolarizing relaxants such as pancuronium, dimethyltubocurarine (metocurine) and dtubocurarine can effect rapid onset of paralysis (Brown et al, 1979). Because of the increased acetylcholine receptors very high doses of these drugs have to be administered to achieve rapid onset of paralysis in burned patients Hagen et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Higher than normal doses of antagonists or nondepolarizing relaxants such as pancuronium, dimethyltubocurarine (metocurine) and dtubocurarine can effect rapid onset of paralysis (Brown et al, 1979). Because of the increased acetylcholine receptors very high doses of these drugs have to be administered to achieve rapid onset of paralysis in burned patients Hagen et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The use of a comparable dose (0.2 mg/kg) of pancuronium is often associated with a much prolonged block. 12 The use of halothane during anaesthesia is associated with prolongation of the block with agents such as p a n c~r o n i u m~~ and t u b o c~r a r i n e l~ and the more recently introduced v e c u r~n i u m .~~'~ The results with atracurium have been variable. While Payne and Hughes1 and Stirt el a/.'"…”
Section: Discussionmentioning
confidence: 99%
“…8 A different group of investigators, however, found this same dose of pancuronium when utilized with fentanyl in a balanced anaesthetic technique produced a heart rate rise of more than 20 per cent above control values in only two of ten patients and it was promptly reversed with additional fentanyl 100-150 ~g. 9 Because of the propensity of narcotics, particularly fentanyl, to produce a centrally mediated reduction in heart rate, 1~ we elected to use pancuronium, a muscle relaxant with vagolytic properties, ~t in a dosage (twice the ED9s ) shown to reliably produce rapid onset of muscular paralysis, a'9 in order to antagonize the fentanyl-induced vagotonia. Succinylcholine was avoided as it would not prevent and might even exacerbate the bradycardia that is produced when fentanyl is administered rapidly and in a large dosage to these patients with a high degree of pre-existing betareceptor blockade.…”
Section: Discussionmentioning
confidence: 99%